2018
DOI: 10.1016/j.ufug.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Plant selection for rain gardens: Response to simulated cyclical flooding of 15 perennial species

Abstract: Plant selection for rain gardens can be complicated, as cyclic flooding and a 4 gradient of moisture level are expected in the depression structure of a rain garden. However, 5 few studies to date have quantified how plant establishment is affected by rain garden 6 moisture dynamics. This study investigated tolerance of 15 candidate perennial species, 7 which experienced flooding cycles consisting of 1-day and 4-day inundation and draining 8 phases. In this study, detection of species suitability using surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
0
29
1
1
Order By: Relevance
“…In our study, this species reached between 41 and 48 cm. For Mis, however, the average heights observed in our study were 38 and 75 cm (for LW and GR, respectively), in the range of those observed by Davidson and Gobin (1998) (20-60 cm), but lower than those reported by other authors: between 70 and 119 cm (Thetford et al, 2011), 134 and 164 cm (Thetford et al, 2009) or an average of 83.6 cm (Yuan and Dunnett, 2018). No references for the other species tested were found.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, this species reached between 41 and 48 cm. For Mis, however, the average heights observed in our study were 38 and 75 cm (for LW and GR, respectively), in the range of those observed by Davidson and Gobin (1998) (20-60 cm), but lower than those reported by other authors: between 70 and 119 cm (Thetford et al, 2011), 134 and 164 cm (Thetford et al, 2009) or an average of 83.6 cm (Yuan and Dunnett, 2018). No references for the other species tested were found.…”
Section: Discussioncontrasting
confidence: 63%
“…Plant selections for rain gardens can be complicated, as cyclic flooding and the gradient moisture level are expected in the depression structure of a rain garden [51]. The rain garden is a green "sponge" used to intercept rainwater [52].…”
Section: Water Rain Management and Mitigationmentioning
confidence: 99%
“…Usually, decreasing moisture gradient towards the edge of the garden is observed. The margin of the garden usually has the highest location (Yuan and Dunnett 2018).…”
Section: Rain Gardensmentioning
confidence: 99%